2015
DOI: 10.1080/13613324.2015.1013460
|View full text |Cite
|
Sign up to set email alerts
|

The power of knowledge: a critical analysis of the depiction of ethnic minorities in China’s elementary textbooks

Abstract: This study critically analyzes knowledge about: (1) ethnic minority groups; (2) the dominant Han group; and (3) the interaction between ethnic minorities and Han presented in three types of elementary textbooks used in China. The analysis reveals that the knowledge about and the values and beliefs of the Han people are overwhelmingly dominant in all reviewed textbooks. At the same time, ethnic minority groups are marginalized and the knowledge about them is incomplete and stereotypical. In addition, most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…As this study has shown, current curriculum materials for the Gymnasium in Hamburg portray the Holocaust from the perspective of native-born German citizens, despite a changing and diversifying population, and a student body that may reflect different needs, perspectives, and understandings of historical events. This finding is consistent with other curriculum research, which proposes that the curriculum reflects the values of the dominant population, while not including other voices (Apple, 1993;Chu, 2015). However, this is particularly relevant given that Hamburg's immigrant population has increased to more than a quarter of the total population in recent years, and xenophobia is also on the rise.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As this study has shown, current curriculum materials for the Gymnasium in Hamburg portray the Holocaust from the perspective of native-born German citizens, despite a changing and diversifying population, and a student body that may reflect different needs, perspectives, and understandings of historical events. This finding is consistent with other curriculum research, which proposes that the curriculum reflects the values of the dominant population, while not including other voices (Apple, 1993;Chu, 2015). However, this is particularly relevant given that Hamburg's immigrant population has increased to more than a quarter of the total population in recent years, and xenophobia is also on the rise.…”
Section: Resultssupporting
confidence: 89%
“…Our methodological approach follows that of other curriculum research, such as that conducted by Bromley and Russell (2010) and Chu (2015;. Specifically, this study used the curriculum materials of a selected Gymnasium in Hamburg, Germany as a qualitative case study of the curriculum of Holocaust education within the highest educational track of the German school system.…”
Section: Conceptual Framework and Methodsmentioning
confidence: 99%
“…Anti-racist legislation is needed to support these changes in textbooks towards interculturality. Chu (2015) noted that dominant groups have more power to legitimise and impose their discourse in institutions, including in educational legislation, so it is necessary to prevent the notion of culture defended in legislation from being constructed as an outcome of inclusionary and exclusionary processes (McConachy, 2018). This requires a synthesised review of the main laws that have given rise to the textbooks analysed.…”
Section: Theorymentioning
confidence: 99%
“…These social injustices were exposed in studies of social conditioning (e.g. Chiu, 2011, Borhaug, 2014, where certain communities were marginalized in the content (Chu, 2015;Eriksen, 2018;Maposa, 2015;Song, 2013;Thompson, 2013;Xiong, 2012), by othering certain groups as less important to national interests (Camase, 2009;Popson, 2001) or less important than an academic pursuit (Lee, 2011a) or government immigration policies (Gulliver, 2010). Considering the interest of one part of this dissertation, to expose social injustices in multimodal discourse, it is important to point out that many of the studies looked at how genders or a groups of people were presented or not presented (graphically and textually), but few mention multimodality in their theoretical frameworks or methodologies, choosing instead to employ unique constructions of analysis (e.g.…”
Section: Critical Studies Of Textbooksmentioning
confidence: 99%